Theoretical Elements in the Approach to Communicative Interactions in the Classroom - Barrientos Córdoba, Adrián (2019)
The present essay it is an approach of the main theoretical elements necessary for the approach of the communicative interactions in the educational field, among which are; the interactions and their types, communication and language, the sociocultural context, the teaching and learning processes and the epistemological traditions. The study of these theoretical elements is the frame of reference that extends the educational fact beyond the transmission of content, seek to visualize the educational act from a holistic level that allows to analyze education from what happens in the classroom.